Was Russia a Colonial Empire? Part 2 - D. Schorkowitz (Nomadic Civilization: Historical Research, 2021)
The translation has been done from the edition: Schorkowitz D. (2019). Was Russia a Colonial Empire? In: Schorkowitz D., Chávez J., Schröder I. (eds.) Shifting Forms of Continental Colonialism: Unﬁnished Struggles and Tensions. Palgrave Macmillan, Singapore. https://doi.org/10.1007/978-981-13-9817-9_5.